Combination of volume‐rendering 3D surface modeling and medical illustration to capture the living fetus. (26th October 2020) - Luks, Francois I.; Collins, Scott; Xia, Jimmy; Cao, Shiliang Alice; Rios, Matthew
Abstract: Objective: A good medical illustration renders essential aspects of a procedure or condition faithfully, yet idealizes it enough to make it widely applicable. Unfortunately, the live fetus is generally hidden from sight, and illustrating it relies either on autopsy material or manipulated newborn images. High‐definition volume rendering of diagnostic imaging data can represent hidden conditions with an almost lifelike realism but is limited by the resolution and artifacts of the data capture. We have combined both approaches to enhance the accuracy and didactic value of illustrations of fetal conditions. Methods: Three examples, of increasing complexity, are presented to demonstrate the creation of medical illustrations of the fetus based on semiautomatic computerized posthoc manipulation of diagnostic images. Results: The end product utilizes the diagnostic accuracy of ultrasound and magnetic resonance imaging of the fetuses and the spatial manipulation of 3D models to create a lifelike, accurate and informative image of the fetal anomalies. Conclusion: Volume‐rendering and 3D surface modeling can be combined with medical illustration to create realistic and informative images of the developing fetus, using a level of detail that is tailored to the intended audience.